ANALISIS KALIBRASI SYRINGE PUMP - Awaluddin Laia; Yulizham Yulizham (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Sustainable health services need to be supported by equipment that is always in a ready-to-use condition and can be functioned properly. One of them is the pumpa syringe tool, through the provision of suitable equipment, preventive maintenance is needed including periodic maintenance and implementation of testing and calibration. The method used in this research is quantitative research with analytical descriptive method which aims to analyze the results of the syringe pump calibration using an infusion pump analyzer and also aims to determine the results of the data obtained after observing the workflow of the tool.From the results of examinations that have been carried out on the syringe pump calibration using the infusion pump analyzer at the Medan Health Facility Security Center (BPFK), the results obtained from the flow rate test of the syringe pump tool at the 10 mL/h point are 9.7 +- 0.4 mLh, so the final result is 9.7 + 0.4 = 10.1 mL/h or 9.7 - 0.4 = 9.3 mL h, it can be concluded that the measurement results that have been made are still within the 10% tolerance limit of the 10 mL/h. Measurement point value Occlusion test the syringe pump tool at the point of 100 mL/h yields 9.97+- 0.4 psi, so the final result is 9.97 + 0,4 = 10.37 psi or 9.97 - 0.4 = 9.57 psi, so it can be concluded that the measurement results that has been doneis still within the tolerance limit of <- 20 psi In performing then calibration.